Archeologia osadnicza w zastosowaniu do badań mikroregionu Graña (Galicja, Hiszpania) - Kmieciński, Jerzy; Kowalczyk, Małgorzata; Walenta, Krzysztof (Acta Universitatis Lodziensis. Folia Archaeologica, 1991)
In 1986 the team of Workers of the Archaeological Institute of Łódź University together with the Archaeological Institute of University of Santiago de Compostela began the common research studies. The subject of investigations of both Universities is devoted to microregional studies on the development of the settlement. The Castro culture limited to Halstatt, Latenian and Roman periods was chosen as a basis for such studies. The research group is interested in the genesis of this culture as well as its further transformations the Middle Ages. Defensive settlements of different size situated on natural hills are characteristic for this culture. The specific feature of Castro culture, at least in its present state investigations, is its long duration (from the VII century B.C. to the II century A.D. and even as others daim to the VI century A.D.). One of topics of many years programme are excavations of Graña Castro situated in the centre of Galicia, 7 km north of Melide town. The subjekt of studies is the use of methods which will allow the reserchers to learn the stratigraphy and the structure of cultural foliation and natural sediments in order to establish the exact chronology and function of the objekt. Excavations were arranged in one row to obtain initial information about all main ponts of the settlement. During the first research season of Graña the fragments of outer defensive stone wall constructed without mortar were discovered. The fragments coming from its inner structure and probably used as dwelling and subsidiary places were discovered as well. Initially two phases of the existence of the settlement with buildings both of oval and rectangular shape were distinguished. The hearth originally a Stove with stone walls and clay mud floor was very interesting. Fragments of pattery both hand-made and made on the grinding stone, clay whorls, glaze beads, gold ear-rings and stone axe most likely used secondarily constitute the antique material. All material allows us to date the exavated layers from the II century B.C. to the II century A.D. Besides excavations; archival and historiographical studies confirming or excluding relations among settlement structures functioning in the period of Roman occupation, in the Middle Ages and in contemporary times in the area of the discussed microregion were conducted as well. Palinologic investigations were begun in order to reconstruct natural environment and its changes in the time course. The number of castro settlements near Melide town is very high. Their mutual time relation is a problem to be explained. If they were existing at the same time then it is possible to reconstruct the territory of economic exploitation of this region assuming that the economy of this region was of farming character. However, these are so far very little documented assumptions which require to be confirmed by detailed studies on few neighbouring settlement morphologically constructing one microregion.